2013
DOI: 10.9755/ejfa.v25i1.9138
|View full text |Cite
|
Sign up to set email alerts
|

A review on role of exogenous enzyme supplementation in poultry<br>production

Abstract: Monogastric animals like poultry, pigs, etc. lack the alloenzymes from rumen microflora and thus it become necessary to incorporate the enzymes in their diets in order to derive optimal nutrient utilization from complex feed matric. Feed enzymes are added to animal feed to increase the availability of nutrient by digesting the feed components during storage or after consumption within the gastrointestinal tract. Some of the enzymes that have been used over the past several years and have potential for use in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Supplementing the diets with exogenous enzymes typically reduces the adverse effects of ANF on non-ruminant animals (Munir & Maqsood, 2013). Microbial proteases are natural protein-digesting enzymes used in pig and poultry nutrition to break down stored proteins and protein-like antinutrients in various plant materials (Ao, 2011;Barletta, 2011).…”
mentioning
confidence: 99%
“…Supplementing the diets with exogenous enzymes typically reduces the adverse effects of ANF on non-ruminant animals (Munir & Maqsood, 2013). Microbial proteases are natural protein-digesting enzymes used in pig and poultry nutrition to break down stored proteins and protein-like antinutrients in various plant materials (Ao, 2011;Barletta, 2011).…”
mentioning
confidence: 99%
“…The digestibility of Ca, P, K, S, Zn, and Fe was also increased by enzyme supplementation, when QB (phytase) was added singly or combined with Axtra XB. It has been reported that the addition of phytase to maize-based diets increases the availability of phytate-phosphorus and other minerals, including Ca, Zn, Cu, and Fe [31, 35]. Similarly, Bradbury et al [36] found that phytase addition to broiler diets improved the digestibility of both Ca and P.…”
Section: Discussionmentioning
confidence: 99%
“…enzymes, such as β-glucanases, amylases, cellulases, xylanases, proteases, galactosidases, protease and lipases, each acting on a certain type of substrate, have been used to reduce the negative nutritional factors on bird performance. However, only carbohydrates (β-glucanases, xylanases, and galactosides) can act as enzyme-substrate complexes, reducing the viscosity of the gastrointestinal system (Munir & Maqsood, 2013), allowing for endogenous enzyme activity, increasing absorption and improving nutrient metabolizability. (Alagawany, Elnesr, & Farag, 2018).…”
Section: Exogenousmentioning
confidence: 99%